Una macchina per produrre dei. Da Heidegger a Bergson - Ronchi, Rocco (Bollettino Filosofico, 2023)
In the Protagoras myth, which inspired twentieth-century reflection on technology, the machine is presented as a prosthesis. It must make up for the “lack” that is distinctive of the human being in contrast to the other living species. Technology is thus included in the horizon of the Aristotelian Poiesis, of work, and is assigned to the human sphere alone. The possibility is feared that the machine could transform man into its appendage, annihilating his sovereignty. In Bergsonian philosophy, machines are instead treated as organs of life, in continuity with the causality of nature. That is, technology is included in the horizon of the Aristotelian Praxis and the human agent is seen as an operator of the natural machine. Mechanics and mysticism share the same vital drive that runs through matter. Thus, Bergson provides the basis for a cosmological consideration of technology (cosmotechnics) and for a “general organology” that is radically opposed to Heidegger’s anthropological-existential conception of technology. Keywords: Cosmotechnics, Homme-Machine, Mysticism, Organology, Power